PENGARUH KOMPETENSI, MOTIVASI, DAN DISIPLIN KERJA TERHADAP KINERJA PENGELOLA BUMDES DI KECAMATAN LAEYA KEBUPATEN KONAWE SELATAN - Samsir, Abdul; Awasinombu, Aidin Hudani; Yusuf, Abdul Razak (Jurusan Manajemen, Fakultas Ekonomi dan Bisnis Universitas Halu Oleo)
This study aims: (1) to determine the effect of competence, motivation and work discipline on the performance of BUMDes employees in Laeya sub-district, Konawe Selatan district simultaneously; (2) To determine the effect of competence on the performance of BUMDes employees in Laeya District, South Konawe Regency: (3) To determine the effect of motivation on the performance of BUMDes employees in Laeya District, South Konawe Regency and; (3) To determine the effect of discipline on the performance of BUMDes employees in Laeya District, South Konawe Regency. The sample in this study was 52 employees or managers of BUMDes in Laeya District, South Konawe Regency. The analysis used is quantitative analysis using Multiple Linear Regression analysis.The results showed that: (1) Competence, motivation, and work discipline had a significant effect on employee performance; (2) Competence has a significant effect on employee performance; (3) motivation has a significant effect on employee performance; (4) Work Discipline has a significant effect on employee performance.